The Anisian ammonoid succession of the Nepal Himalaya - Waterhouse, J. B. (Journal of Nepal Geological Society, 1996)
Anisian ammonoid sequences are well developed in central Nepal, north of the Annapurna Range, extending from the Manang district through Puchenpra Ridge, Plateau of lakes, Mesokanto Pass, to the Kali Gandaki Valley. The earliest and most significant faunules are developed in two zones, in the Kaisang, Tangje, and Thorong Members of the upper Gungdang Formation. The older zone is dominated by Grambergia, and also contains species of Ananorites, Tienjunites, Qilianshanites, Pearylansites,and Sturia? with other genera. The upper zone contains over 30 species, with Lenotropites, Beyrichitids, Arctohungarites, Norites, Longobardites, Epiczekanowskits, Stenopopanoceras and Neopopanoceras? These zones overlie a late Scythian faunule with Keyserlingites, Dagnoceras, Prohungrites, Nordophiceras and Svalbardiceras etc, placed in turn above a rich ammonoid faunule with Subcolumbites, Dinarites, Paranoritoides, Eophyllites, Albanites and other genera. The Kaisang-Thorong zones are followed by a suite of ammonoids belonging to the Paracrochordiceras Zone; or Aegean Stage, generally regarded in recent years as indicating basal Anisian. Thus the Nepal sequence indicates the presence of a post-Scythian, pre-Aegean stage, here informally named Manasluan, after Mt. Manaslu , which is prominent west of the type section for both stratigraphic and biostratigraphic entities, on the southeast ridge of Mt. Chulu. The Manasluan stage is poorly developed world-wide, but may be represented, in part, by the so-called Lenotropites qinghaiensis faunule of central Qighai, and Neopopanoceras haugi Zone of California and Nevada. The Paracrochordiceras Zone of Nepal is represented by two successive faunules with some 20 species in the Phukung Menmber at the top of the Gungdang Formation and in the overlying lower Mukut Group, and includes two species of Paracrochordiceras. The Bithynian Stage follows, with a meagre, Gymnites depauperatus faunule, succeeded by a rich Paradanubites-Holandites-Aristoptychites-Gymnites assemblage of over 30 species. Several of the species are shared with Diener's "Lower Muschelkalk" Ammonoids from the northwest Himalaya, and some of the species are found also in Diener’s "Upper Muschelkalk" Keyserlingites is present at this level, as reported by Diener in his "Lower Muschelkalk" Nepal evidence suggests that this genus, or species very close to this genus, range from the Subcolumbites level in Nepal, i.e. late Scythian, into middle Anisian, or Bithynian. North American authorities have endeavoured to impose a short range for Keyserlingites, as latest Scythian, but this appears to be wrong. Their interpretation of the Scythian-Anisian boundary therefore has to be substantially re-evaluated. In the younger Mukut Group of the Annapurna region there is a possibility of having Bulogites and Balatonites, indicating the presence of Pelsonian Stage. Apart from this, Ladinian ammonoids have also been found, encouraging further study. From the Mukut of (northwest Nepal) in west Dolpo, equivalent of Diener's Upper Muschelkalk," or Illyrian Stage, with Paraceratites of the trinodosus format, and Pseudodanubites, Hollandites, Beyrichites, Gangadharites, Bulogites, Ptyshites, Discoptydhites, Monophyllites and other genera have been collected. These studies indicate that Anisian of Nepal is moderately well developed, and offer sequences particularly significant for the Scythian-Anisian boundary, and lower Anisian. They also help resolve the long standing dispute over the age of Keyserlingites, which has clouded understanding of the Anisian and Scythian for several decades.